2015
DOI: 10.1021/acs.biochem.5b00785
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Aglycon-Recognizing Sites of UDP-glucose:glycoprotein Glucosyltransferase by Means of Squarate-Mediated Labeling

Abstract: Because of its ability to selectively glucosylate misfolded glycoproteins, UDP-glucose:glycoprotein glucosyltransferase (UGGT) functions as a folding sensor in the glycoprotein quality control system in the endoplasmic reticulum (ER). The unique property of UGGT derives from its ability to transfer a glucose residue to N-glycan moieties of incompletely folded glycoproteins. We have previously discovered nonproteinic synthetic substrates of this enzyme, allowing us to conduct its high-sensitivity assay in a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…S5 ), implying its possible contribution to the folding-sensing mechanism of the catalytic domain. An affinity labelling experiment suggested that the catalytic domain is involved in interaction with a hydrophobic aglycon 15 .
Figure 2 Crystal structure of C-terminal catalytic domain of UGGT.
…”
Section: Resultsmentioning
confidence: 99%
“…S5 ), implying its possible contribution to the folding-sensing mechanism of the catalytic domain. An affinity labelling experiment suggested that the catalytic domain is involved in interaction with a hydrophobic aglycon 15 .
Figure 2 Crystal structure of C-terminal catalytic domain of UGGT.
…”
Section: Resultsmentioning
confidence: 99%
“…It is a large monomeric protein of more than 1500 residues and found in almost all eukaryotes. The activity of UGGT has been probed using native and misfolded glycoproteins (7, 10 -13), glycopeptides (14 -16), and small synthetic substrates (17)(18)(19)(20)(21)(22). These studies have shown a strong selectivity for glucosylation of misfolded over folded substrates.…”
mentioning
confidence: 99%
“…Indeed, glycopeptides with clusters of hydrophobic amino acids were substrates of UGGT . In addition, our analysis revealed a hydrophobic patch on the surface of UGGT . Accordingly, it was anticipated that UGGT accepts hydrophobic tagged glycoproteins as substrates.…”
Section: Figurementioning
confidence: 99%
“…In this respect, a crystallographic study by Zhu and Kato is revealing, as it clarified the presence of a hydrophobic patch on its thioredoxin‐like domain 3 (Trx‐3), which was suggested to be a folding sensor region. On the other hand, our recent study, which employed an electrophilic functionalized glycan probe, identified a cluster of hydrophobic amino acids (which could function as folding sensing), in the C‐terminal catalytic region of the enzyme . As UGGT is likely to encounter a variety of glycoprotein substrates, multiple folding‐sensor regions are quite likely.…”
Section: Figurementioning
confidence: 99%